EFFECT OF SURFACE DEAD-LAYER QUENCHING ON THE THIRD-ORDER NONLINEAR OPTICAL PROPERTIES OF NANOPARTICLES - Koraboev, Kamoliddin Abdushukurovich (SCIENCE and SOCIETY, 2026)
To resolve the discrepancy between theory, which predicts a monotonic increase of the third-order nonlinear optical susceptibility (χ⁽³⁾) of CdSe quantum dots as the radius R decreases, and experiment, which shows sharp quenching below R < 2 nm, an analytical model combining the Boyd and Brus formalisms with a surface “dead-layer” correction is proposed. The model predicts a non-monotonic χ⁽³⁾(R) dependence and an optimal radius Ropt ≈ 2.5 nm at which the susceptibility is maximal. The computed values (10⁻²⁰ − 10⁻²² m²/V²) are in order-of-magnitude agreement with the CdSe/ZnS-MOF theoretical estimate and CdTe DFWM measurements, and are within two orders of magnitude of the single directly comparable Z-scan measurement on isolated colloidal CdSe quantum dots.